(untitled) (Revista de Ciências Agroveterinárias, 2008)
When the phytopathogenic bacteria associate to plant leaves, they use several strategies for colonization. The colonization stages vary from modification of the environment on the leaf surface, formation of aggregates, entrance in the host, and its return to the leaf surface. This literature review addresses biological aspects of the colonization of bacteria causing phytopathogenic foliar diseases, describing common features and some particular aspects of certain bacteria.